Study of pharmacological activity of dry extract of Sakhalin willow shoots against the background of experimental thrombophlebitis - Maloshtan, Ludmila; Artemova, Kateryna; Borodina, Nataliia; Kukhtenko, Oleksandr (РС тесhnology сеntеr, 2023)
The objective of the research was to study the pharmacological activity of dry extract of Sakhalin willow shoots – DEWS against the background of experimental thrombophlebitis. Materials and methods. Dry extract of Sakhalin willow shoots (DEWS) was the object matter of the present research and served as a therapeutic and prophylactic agent. In the experiment conducted, rabbits weighing 2.0–2.5 kg were used. The animals were divided into three groups. Group 1 was a control group; group 2 were animals that had been intragastrically injected with DEWS at a dose of 30 mg/kg prior to modelling thrombophlebitis; group 3 similarly received Eskuvit 20 mg/kg as a reference drug – pills (JSC Halychpharm, Ukraine). The dose for animals was recalculated, taking into account body weight according to the Rybolovlev method. Experimental thrombophlebitis was caused by injecting an intravenous solution of 2 % lugol at a dose of 0.1 ml into the marginal vein of the ear. Statistical data processing was carried out using the Statistica for Windows 11.0 program based on variance analysis for repeated measurement data using the Mann-Whitney criteria at a probability level of p<0.05. Results. Against the background of the development of experimental thrombophlebitis in rabbits, the development of thrombosis of the ear vein and the inflammatory process of adjacent tissues were observed. The inflammatory process was accompanied by pronounced hyperemia and oedema. Prophylactic administration of DEWS for 6 days contributed to a decrease in the inflammatory process already on the 5th day of observation. The area of the injured area was 20 % smaller than in the control pathology group. The therapeutic and prophylactic effect of herbal medicine can be explained by the content of flavonoids and salicylates in its composition. Eskuvit showed a less pronounced thrombolytic effect in terms of its influence on thrombosis and thrombolysis. Conclusions. The administration of DEWS in the therapeutic and prophylactic regimen at a dose of 30 mg/kg has a pronounced anti-inflammatory, thrombolytic and venoprotective effect in experimental peripheral venous thrombophlebitis in rabbits. The results of the studies obtained allow us to recommend DEWS as a promising venoprotective agent with thrombolytic activity.
Keywords: dry extract of Sakhalin willow shoots; experimental thrombophlebitis; inflammatory process; pharmacological activity; rabbits